Pancreaticoduodenectomy in octogenarians: The importance of "biological age" on clinical outcomes. (March 2022) - Quero, Giuseppe; Pecorelli, Nicolò; Paiella, Salvatore; Fiorillo, Claudio; Petrone, Maria Chiara; Capretti, Giovanni; Laterza, Vito; De Sio, Davide; Menghi, Roberta; Kauffmann, Emanuele; Nobile, Sara; Butturini, Giovanni; et al.
Abstract: Introduction: With the prolongation of life expectancy, an increasing number of elderly patients are evaluated for pancreatic surgery. However, the influence of increasing age on outcomes after pancreaticoduodenectomy (PD) is still unclear, especially in octogenarians. Aim of this study is to evaluate the perioperative characteristics and outcomes of octogenarians undergoing PD. Methods: Data for 812 patients undergoing PD between 2019 and 2020 in 10 referral centers in Italy were reviewed. Patients aged 80 years or older were matched based on nearest neighbor propensity scores in a 1:1 ratio to patients younger than 80 years. Propensity scores were calculated using 7 perioperative variables including gender, ASA score, neoadjuvant treatment (NAT), biliary stent positioning, type of surgical approach (open, laparoscopic, robot-assisted), associated vascular resections, type of lesion. Perioperative characteristics and short-term postoperative outcomes were compared before and after matching. Results: Overall, 81 (10%) patients had 80 years or more. Before matching, octogenarians had a higher rate of ASA score≥ 3 (n = 35, 43.2% vs. n = 207, 28.3%; p = 0.005) and less frequently underwent NAT (n = 11, 13.6% vs. n = 213, 29.1%; p = 0.003). Matching was successfully performed for 70 octogenarians. After matching, no differences in preoperative and intraoperative characteristics were found. Postoperatively, ICU admission was more frequent in octogenarians (50% vs 30%; p = 0.01). Although in-hospital mortality was higher in octogenarians before matching (7.4% vs 2.9% in the younger cohort; p = 0.03), no difference was noted between the matched cohorts (p = 0.36). Postoperative morbidity was comparable between groups in the whole and selected populations. At the multivariate analysis, chronological age was not recognized as a prognostic factor for cumulative major complications, while ASA ≥3 was the only confirmed influencing feature (OR 2.98; 95%CI: 1.6–6.8; p = 0.009). Conclusio: In high-volume centers, PD in octogenarians shows similar outcomes than younger patients. Age itself should not be considered an exclusion criterion for PD, but a focused preoperative assessment is essential for adequate patient selection. Highlights: Few data are present on perioperative outcomes of octogenarians after pancreaticoduodenectomy. When appropriately selected, octogenarians present similar outcomes to younger patients. Multivariate analysis evidenced ASA score ≥3 as the only negative feature for the clinical course. Chronological age should not be considered an absolute exclusion criterion for pancreaticoduodenectomy.